THE IMPACT OF CORPORATE GOVERNANCE ON THE QUALITY OF EXTERNAL AUDITING: A STUDY ON IRAQI COMMERCIAL BANKS - Hasan Sahab Mutar; Dorsaf Ben Aissia (American Journals, 2024)
This paper examines the importance of shedding light on the extent to which Iraqi commercial banks adhere to the rules and mechanisms of corporate governance. Obtaining 168 correct forms after excluding the incorrect answers, and the questionnaire was directed to a sample of shareholders (owners), external auditors and academics. Our study shows that the board of directors and audit committees have an important role in supporting the internal auditor to perform his work efficiently and effectively, which is reflected and positively impacted on the quality of the performance of the external auditor, as the external auditors play the role of the assessor of the banking supervisory system, identifying and revealing weaknesses and strengths in it.
Keywords: Corporat e-governance, audit exterior, quality.